Dynamic surface behavouir and aqueous foam properties of graphene- polystyrene sulfonate / Cetyl trimethylammonium bromide mixtures - Ali Akbar Ghofrani; Mahmoodreza Khadangi-Mahrood; Zahra Hejri; Susan Khosroyar (Heliyon)
An interface can be delicately designed using interactions between nanoparticles and surfactants by controlling surface properties such as activity and charge equilibrium. This study seeks to provide insights into how surfactant concentration impacts the stability and dynamics of nanoparticle-surfactant interfaces, with potential applications in material science and interface engineering. This study investigates the interactions between Graphene Function (Gr, Graphene function in this text refers to functionalizing the graphene sheets with –COOH groups via acidic reactions.), Polystyrene sulfonate (PSS), and the surfactant Cetyl trimethylammonium bromide (CTAB) at the air/water interface. We examined various ratios of CTAB to Gr-PSS to determine the effects of surfactant concentration, focusing on conditions up to the critical micelle concentration (CMC). Specifically, we utilized different concentrations of CTAB ranging from 0 to 1 CMC (0.82 mM), while the concentration of Gr-PSS varied between 0 and 1 wt% and 20–50 ppm. To analyze the dynamic interfacial properties, including dynamic surface tension and dilational viscoelasticity, we employed drop profile analysis tensiometry (PAT) to measure area perturbation frequency at the air/water interface. The study aimed to elucidate the behavior of the CTAB/Gr-PSS complex at this interface. We discussed the adsorption of the CTAB/Gr-PSS complex on the droplet surface and its varying roles by examining surface pressure across different area change domains and conducting elasticity measurements. The results indicate that the attachment of CTAB molecules to Gr particles and PSS leads to the formation of surface-active complexes. As the surfactant concentration increases, excess CTAB monomers compete with the CTAB/Gr-PSS complexes for access to the interfaces, causing the larger complexes to migrate into the liquid bulk, as confirmed by elasticity assessments.